2010
DOI: 10.1061/(asce)0733-9496(2010)136:2(268)
|View full text |Cite
|
Sign up to set email alerts
|

Urban Storm-Water Quality Management: Centralized versus Source Control

Abstract: Abstract:The continuous growth of urban areas and the increasing public awareness of the environmental impacts of storm water have raised interest on the quality of the receiving water bodies. In the past two decades, many efforts have been directed at improving urban drainage systems by introducing mitigation measures to limit the negative environmental impacts of storm water. These mitigation measures are generally called best management practices ͑BMPs͒, sustainable urban drainage systems, or low impact dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The authors found that the LID site design generated much lower runoff volumes, provided more recharge and provided more resilience to changes in extreme events; the same is suggested in Pyke et al (2011). On the other hand, Freni et al (2010) evaluated distributed or source controls (LID) versus centralized storage for mitigating CSOs using a simulation model. The authors found that centralized controls were more robust.…”
Section: Introductionmentioning
confidence: 92%
“…The authors found that the LID site design generated much lower runoff volumes, provided more recharge and provided more resilience to changes in extreme events; the same is suggested in Pyke et al (2011). On the other hand, Freni et al (2010) evaluated distributed or source controls (LID) versus centralized storage for mitigating CSOs using a simulation model. The authors found that centralized controls were more robust.…”
Section: Introductionmentioning
confidence: 92%
“…The effectiveness of LID practices for small storms was also presented in Ackerman and Stein [10], Carter and Jackson [11], Schneider and McCuen [14], etc. In addition, the effects of LID practices were evaluated differently according to locations, numbers, and types of LID practices [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate adverse hydrological and water quality impacts of rapid urbanization, a number of stormwater management techniques have been developed and adopted, but there is still a significant debate over the best approaches (Freni et al 2010;Burns et al 2012;Shuster & Rhea 2013). An increasingly attractive approach is decentralization and source control which uses a limited number of control measures distributed throughout a catchment (Booth & Jackson 1997).…”
Section: Introductionmentioning
confidence: 99%